Aportes de la Historia y la Filosofía en la enseñanza de las ciencias a partir de la actividad experimental asociada a la hidráulica - Almeida Sánchez, Helga; García Arteaga, Edwin Germán (Góndola, Enseñanza y Aprendizaje de las Ciencias, 2022)
This paper collects advances in the research project on the history and philosophy of sciences in physics teaching,focused on hydraulics. The research question regarding social needs, inequality, and social vulnerability during the first quarter of the 21st century is; What physics to teach today? And for what purpose are hydraulics? The document recognizes the historical importance of experimental activity in science, the associated phenomenology, and the conceptual richness behind it, which, in general, has been very limited at the educational level. Nor is it appreciated how the historical perspective of science favors the understanding of the world and it is a contribution to current social problems. Regarding the hydraulics teaching, the absence of experimental activity is evident. Concepts such as pressure, speed, continuity, and Bernoulli's principle are taught through processes of memorization and application of meaningless mathematical algorithms and without impact on the daily lives of students. The research project proposes to re-contextualize the experimental activity associated with hydraulics, as well as its formalization processes, from the concerns of scientists such as Archimedes, Pascal, Da Vinci, and Bernoulli, among others, who contributed to the construction of meaning and significance of the phenomenon under study. In this sense, the objective is to collect and analyze the historical documentation of hydraulics and to carry out a critical historical analysis of the text of Johan Bernoulli Hydraulics and its predecessors to finally, from a science didactics approach, propose core activities around the problems registered for the teaching of hydraulics in the initial training teachers in this field.